Los contenidos de redes sociales y la teoría de los usos y gratificaciones en estudiantes de la utmach. - Hidalgo Vanegas, Melissa Jackeline; Suarez Serrano, Jorge Gabriel (Machala, 2023)
This work is based on the Theory of Uses and Gratifications and its application in the digital age, specifically to networks. It was born from the consideration of this theory being applied to traditional media, however social networks have also become spaces that allow information and interaction at the same time in these new times. Considering McQuail's gratifications: fun, social relationships, vigilance, and personal identity; It is proposed that networks are not indifferent to satisfying these needs. For this reason, the three most used networks in Ecuador were selected: Facebook, Instagram and TikTok to know the characteristics and needs they satisfy according to the public. Thus, the objective was raised to analyze the content of social networks in relation to the Theory of Uses and Gratifications in the students of the Technical University of Machala to understand usage and consumption trends that can be applied to strategies in the local context. For this analysis of social network content, a non-experimental and mixed field design methodology was used. It uses three research techniques: interviews, surveys and qualitative content analysis. The interviews were carried out with three professionals. The first is a psychologist, Ronald Pinta, to delve into the psychological bases of the theory and how it is reflected today in the use and consumption of social networks. On the other hand, the second goes to the researcher Fátima Martínez, who provided her knowledge on the subject having written similar articles and detailing how gratifications are presented in the digital age. The third to Alba Granda, a sociologist who provided a perspective from a different field of study with a focus on network interactions and their culture. On the other hand, the surveys were aimed at studies to find out: demographic data, uses and gratifications on social networks, and the creation and dissemination of their own content on the networks. Information was obtained on associated uses, formats, contents, differentiating elements. From this information, content analysis matrices were created to classify the content based on the audience, analyzing 3 accounts per social network. The results obtained are characteristics and attributions of the public to these networks that allow the creation of more effective and better targeted content. In this way, on Facebook it is ideal to create publications with humorous content, characterized by the text format. On Instagram, they highlight images with personal narratives sharing their identity. On TikTok, videos with creative trends, dances or fashion stand out. The content that they mostly consume and that they believe attracts more locally is humorous and this is followed by gratification with news or updated information. Information is also obtained from your use of networks. It is established that young people have migrated from networks. Despite having accounts on the aforementioned networks, most of them have abandoned Facebook, spending less than 1 hour on it. While most of the time it is used on TikTok. Above all, regarding its consumption, it is discovered that the element that young people consider differentiating for their generation is the short duration of the content, being more summarized or brief.
El presente trabajo se respalda en la Teoría de Usos y Gratificaciones y su aplicación en la era digital, específicamente a las redes. Nace a partir de la consideración de esta teoría siendo aplicada a medios tradicionales, sin embargo las redes sociales también se han convertido en espacios que permiten información e interacción al mismo tiempo en estos nuevos tiempos. Considerando las gratificaciones de McQuail: diversión, relaciones sociales, vigilancia e identidad personal; se plantea que las redes no son indiferentes a satisfacer estas necesidades. Por ello, se seleccionó a las tres redes más usadas en Ecuador: Facebook, Instagram y TikTok para conocer las características y necesidades que satisfacen según el público. Fue así que se planteó el objetivo analizar el contenido de las redes sociales en relación con la Teoría de Usos y Gratificaciones en los estudiantes de la Universidad Técnica de Machala para la comprensión de tendencias de uso y consumo que puedan ser aplicadas para estrategias en el contexto local. Para este análisis de los contenidos de redes sociales, se utilizó una metodología de diseño de campo de tipo no experimental y mixta. Utiliza tres técnicas de investigación: entrevistas, encuestas y análisis cualitativo de contenido. Las entrevistas se realizaron a tres profesionales. El primero un psicólogo, Ronald Pinta, para ahondar en las bases psicológicas de la teoría y cómo se refleja a día de hoy en el uso y consumo de redes sociales. Por otro lado, la segunda a la investigadora Fátima Martínez, quien brindó su conocimiento en el tema al haber realizado artículos similares y detallando de qué manera se presentan las gratificaciones en la era digital. La tercera a Alba Granda, socióloga que proporcionó una perspectiva desde un campo de estudio distinto con enfoque a las interacciones en redes y su cultura. Por otro lado, las encuestas estuvieron dirigidas a los estudios para conocer: datos demográficos, usos y gratificaciones en redes sociales, y la creación y difusión de sus propios contenidos en las redes. Se obtuvo información sobre los usos asociados, formatos, contenidos, elementos diferenciadores. De esta información, se crearon matrices de análisis de contenido para clasificar los contenidos en función del público, analizando 3 cuentas por red social. Los resultados obtenidos son características y atribuciones del público a estas redes que permiten crear contenido más eficaz y mejor direccionado. De este modo, en Facebook es ideal la creación de publicaciones con contenido humorístico siendo caracterizada por el formato texto. En Instagram, resaltan imágenes con narrativas personales compartiendo su identidad. En TikTok, se destacan los videos con tendencias creativas, bailes o moda. Los contenidos que mayormente consumen y que creen que atraen más a nivel local son humorísticos y a esto le sigue la gratificación vigilancia con noticias o información actualizada. También se obtiene información de su uso de las redes. Se establece que los jóvenes han migrado de redes. A pesar de tener cuentas en las redes mencionadas, la mayor parte tiene en abandono a Facebook pasando menos de 1 hora en ella. Mientras que la mayoría del tiempo se utiliza en TikTok. Sobre todo, en cuanto a su consumo, se descubre que el elemento que los jóvenes consideran diferenciador para su generación es la corta duración de los contenidos, siendo más resumidos o breves.
Keywords: REDES SOCIALES; CONTENIDO DIGITAL; TEORIA DE USOS Y GRATIFICACIONES; GENERACION Z; CULTURA DIGITAL